From Cash to Clicks: Examining the Effects of E-Wallet Usage on Financial Literacy, Spending Behavior, Financial Stress, and Well-Being Among Malaysian Undergraduates - Daisy Mui Hung Kee; Amsyar Nurhakim Bin Abdul Rashid; Alvin Tieu Kiu Fu; Ang Jun Zhe; Arissa Sorfena Binti Allias (AIBPM Publisher, 2025)
This study investigates how e-wallet usage affects financial literacy, spending behavior, financial stress, and financial well-being among Malaysian undergraduates. Using a quantitative, cross-sectional survey design, data were collected from 200 students across public and private universities using an online questionnaire distributed via Google Forms. The results analyzed through SPSS 26 involved descriptive statistics, Pearson correlation, and multiple regression. The findings revealed significant positive correlations among all variables (p .01). Regression results showed that financial literacy (? = 0.751, p .001) and spending behavior (? = 0.074, p .05) significantly influenced financial well-being, explaining 62.8% of the variance (R² = 0.628). Conversely, e-wallet usage (? = -0.022) and financial stress (? = 0.105) were insignificant predictors. The study concludes that while digital payment systems enhance financial access, their impact on financial stability depends heavily on financial literacy and responsible spending. These findings imply that universities should integrate financial literacy education into digital finance programs to ensure balanced e-wallet usage and improved student financial well-being.